1992
DOI: 10.1016/0882-4010(92)90048-s
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of Escherichia coli serotype O6 strains from urinary tract infections

Abstract: combinations of capsule ( K) and flagellin ( H) antigens, were analysed according to the outer membrane pattern (OMP), serum resistance properties, mannose-resistant hemagglutination using various types of erythrocytes, and also for the genetic presence and the expression of Pfimbriae. S fimbriae/F1 C fimbriae, Type 1 fimbriae, aerobactin and hemolysin. Twenty selected strains were further analysed by pulsed field gel electrophoresis (PFGE), elaborating genomic profilas by Xba I cleavage and subsequent Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Sixteen strains were isolated from humans with septicemia: eight from the blood of newborns without meningitis (61), seven from adults with septicemia in France (this study), and one from a septicemic patient in Hungary (10). Fifteen strains were from urinary tract infections, including one strain from Hungary (10), five from Germany (68,69), six from the ECOR collection (44) (http://foodsafe.msu.edu/whittam/ecor), and the UPEC type strains CFT073, 536, and J96 (22,43,62). Four animal ExPEC strains were isolated from cases of septicemia in a sheep (S5), a pig (P72), and calves (BM2-1 and Orne6) (9,13,45,56).…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen strains were isolated from humans with septicemia: eight from the blood of newborns without meningitis (61), seven from adults with septicemia in France (this study), and one from a septicemic patient in Hungary (10). Fifteen strains were from urinary tract infections, including one strain from Hungary (10), five from Germany (68,69), six from the ECOR collection (44) (http://foodsafe.msu.edu/whittam/ecor), and the UPEC type strains CFT073, 536, and J96 (22,43,62). Four animal ExPEC strains were isolated from cases of septicemia in a sheep (S5), a pig (P72), and calves (BM2-1 and Orne6) (9,13,45,56).…”
Section: Methodsmentioning
confidence: 99%
“…As UPEC clinical strains, we used E. coli J96 (17) and an isolate (RZ422) from the collection of the "Institut für Molekulare Infektionsbiologie der Universität Würzburg" obtained from patients suffering from either cystitis or pyelonephritis (39). E. coli LE392 was transformed using either a pISS391 cosmid or empty vector pHC79 (20), resulting in the K12/cnf1 ϩ strain and LE392/pHC79, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The sheA gene was deleted in the 14 uropathogenic E. coli (UPEC) strains examined by Ludwig et al in a recent study (16). Their 14 UPEC strains, including the well-known hlyA ϩ J96 and 536 strains, were assayed for the presence of an hlyA fragment by Southern blot hybridization, but it was identified in only 10 of the 14 strains (28,29). In our study, we found that 47.1% of the 486 UPEC strains contained the sheA gene ( Table 3).…”
mentioning
confidence: 99%